The Effectiveness of Cognitive Strategy to Improve Students’ Listening Comprehension Achievement - Damayanti, Alya; Angraini, Nike; Surayatika, Desi (International Journal of English Education and Linguistics (IJoEEL), 2023)
Listening plays an important part of the learning process because it can help students understand and respond according to the material presented by the teacher. According to Lafi (2001) a highly integrative talent is listening comprehension. It is crucial to the process of learning or acquiring a language since it helps the development of other language abilities. Thus, the purpose of this study is to find out the use of cognitive strategies on students' listening comprehension and also to find the average difference between students who are taught by using cognitive strategies and those who are not. The purpose of this study is to see how the cognitive process affects students' progress in listening comprehension. This research uses quantitative methods with a research sample used as many as 67 people. 33 people in the experimental class and 34 people in the control class who are students from SMP N 38 Palembang using purposive sampling. Based on the results of research conducted by researcher, researcher found a significant difference in student learning outcomes in classes taught using cognitive strategy methods (experimental class) and classes that were not taught using cognitive strategy methods (control class). Testing to find problems in this study using the Mann-Whitney and Wilcoxon tests. In conclusion, cognitive strategies allow students, especially in SMP N 38 Palembang to effectively improve their listening skills.